PENGARUH KEGIATAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) TERHADAP AKTIVITAS BELAJAR SISWA - Ibrahim, Juliyanti; Hafid, Radia; Toralawe, Yulianti; Mahmud, Melizubaida; Koniyo, Rierind (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aimed to determine the effect of Student Council (OSIS) activities on students’ learning activities at SMP Negeri 1 Kabila. The background of this study was based on the importance of learning activities in the learning process and the fact that students’ involvement in organizational activities can have both positive impacts and challenges on learning, such as increasing leadership experience, responsibility, and cooperation, while also potentially causing fatigue, reduced study time, and decreased concentration. This research employed a quantitative approach with a correlational design. The population consisted of all 35 members of the student council at SMP Negeri 1 Kabila, and the entire population was used as the sample. Data were collected through questionnaires, while the data analysis techniques included validity testing, reliability testing, normality testing, simple linear regression, t-test, Pearson correlation, and coefficient of determination. The results showed that student council activities had a positive and significant effect on students’ learning activities, with a t-value of 5.697 greater than the t-table value of 2.030 and a significance value of 0.000. The correlation coefficient of 0.704 indicated a strong relationship, while the coefficient of determination of 0.496 showed that 49.6% of the variation in students’ learning activities was explained by student council activities. Thus, the better the students’ involvement in student council activities, the better their learning activities. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh kegiatan Organisasi Siswa Intra Sekolah (OSIS) terhadap aktivitas belajar siswa di SMP Negeri 1 Kabila. Latar belakang penelitian ini didasarkan pada pentingnya aktivitas belajar dalam proses pembelajaran serta adanya kenyataan bahwa keterlibatan siswa dalam kegiatan organisasi dapat memberikan dampak positif maupun kendala terhadap belajar, seperti meningkatnya pengalaman kepemimpinan, tanggung jawab, dan kerja sama, tetapi juga berpotensi menimbulkan kelelahan, berkurangnya waktu belajar, dan menurunnya konsentrasi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian adalah seluruh anggota OSIS SMP Negeri 1 Kabila yang berjumlah 35 siswa, dan seluruh populasi dijadikan sampel. Pengumpulan data dilakukan melalui angket, sedangkan analisis data menggunakan uji validitas, uji reliabilitas, uji normalitas, regresi linear sederhana, uji t, korelasi Pearson, dan koefisien determinasi. Hasil penelitian menunjukkan bahwa kegiatan OSIS berpengaruh positif dan signifikan terhadap aktivitas belajar siswa, dengan nilai thitung 5,697 lebih besar dari ttabel 2,030 dan nilai signifikansi 0,000. Koefisien korelasi sebesar 0,704 menunjukkan hubungan yang kuat, sedangkan koefisien determinasi sebesar 0,496 menunjukkan bahwa 49,6% variasi aktivitas belajar siswa dijelaskan oleh kegiatan OSIS. Dengan demikian, semakin baik keterlibatan siswa dalam kegiatan OSIS, semakin baik pula aktivitas belajar siswa.